2006
DOI: 10.1002/nur.20116
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of distress in caregivers of persons with a primary malignant brain tumor

Abstract: The purpose of this cross-sectional, descriptive study was to identify predictors of distress for family caregivers of persons with a primary malignant brain tumor (PMBT). The effect of the care recipient's functional, cognitive, and neuropsychiatric status on caregiver burden and depressive symptoms was examined through telephone interviews with 95 caregivers. Care recipients' neuropsychiatric status consistently affected caregivers' depressive symptoms and burden, and assisting with activities of daily livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
128
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 55 publications
4
128
1
Order By: Relevance
“…Cognitive deficits create care demands for the caregivers and increase the number of tasks with which the caregiver must render assistance. In patients with primary brain tumors, cognitive dysfunction has been consistently linked to increased caregiver demands [46] and when compared with functional status, cognitive status was found to be a much stronger predictor of caregiver burden [47].…”
Section: Discussion Cognitive Impairment Among Patients With Brain Mementioning
confidence: 99%
“…Cognitive deficits create care demands for the caregivers and increase the number of tasks with which the caregiver must render assistance. In patients with primary brain tumors, cognitive dysfunction has been consistently linked to increased caregiver demands [46] and when compared with functional status, cognitive status was found to be a much stronger predictor of caregiver burden [47].…”
Section: Discussion Cognitive Impairment Among Patients With Brain Mementioning
confidence: 99%
“…Cognitive changes result in short-term memory loss, reduced attention, personality changes and altered mood (Weitzner, 1999). In an interview study of 95 caregivers of people with a PMBT, Sherwood et al (2006) report many concerns such as worries about short-term memory problems, and patients' diffi culties in making decisions. In another study the most commonly reported neuropsychiatric symptoms were depression, irritability, night time disturbances, apathy and hallucinations (Klein et al, 2001).…”
mentioning
confidence: 99%
“…3 Also, glioma patients frequently develop a loss of independence. When compared with other cancer populations, glioma patients have higher rates of dependent status, 29 and their need for assistance with activities of daily living such as dressing, walking inside the home, and bathing increases the burden on their caregivers. 29 Difficulties with daily activities are less frequently reported by others caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with other cancer populations, glioma patients have higher rates of dependent status, 29 and their need for assistance with activities of daily living such as dressing, walking inside the home, and bathing increases the burden on their caregivers. 29 Difficulties with daily activities are less frequently reported by others caregivers. 30 Certainly, a high burden has already been associated with caring for family members with complex care needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation